Pre-Operative Versus Post-Operative Kinematic Assessment and Functional Outcomes of the Thoracohumeral Joint in Adults with Rotator Cuff Tears - (:unkn) unknown (My University, 2018)
PRE- OPERATIVE VERSES POST-OPERATIVE KINEMATIC ASSESSMENT OF THE THORACOHUMERAL JOINT IN ADULTS WITH ROTATOR CUFF TEARS by Margaret E. French The University of Wisconsin-Milwaukee, 2018 Under the Supervision of Brooke A. Slavens, PhD This project investigated upper extremity (UE) motion and functional outcomes before and after full-thickness supraspinatus rotator cuff (RC) repair through kinematic analyses of three Activities of Daily Living (ADL) tasks. RC repair is a standard procedure known to alleviate pain, weakness, and stiffness, with improvements of decreased pain and increased range of motion (ROM). Eight (8) subjects (63.6 ± 6.3) with a supraspinatus RC tear participated in this study. Three ADLs were recorded and analyzed at the UWM Mobility Lab using a 15 camera motion capture system. Shoulder health outcome scores (ASES) were taken at each session to determine patients’ pain and perceived functionality of the surgical shoulder. Testing took place two times: 0-12 weeks prior to surgery and 9-12 weeks after surgery. There was not a significant difference of the thoracohumeral joint abduction/adduction ROM pre-to-post-operatively during the crossbody task (P=0.012). No differences in ROM pre-to-post-operatively of the surgical shoulder during the hair comb and reach to back pocket tasks may be due to capsular tightness occurring at the 3 month follow up window. Also, no difference between the surgical and non-surgical abduction/adduction ROM pre-operatively may be due to a wash out effect of the subjects due to tendon involvement. Subjects may need to be analyzed based on number of tendons involved due to the difference in ROM between group A and B. No change in ASES scores may be due to the follow up window being too soon in the rehabilitation process and should be investigated at a longer follow up window.
Keywords: Adults; Functional Outcomes; Kinematics; Rotator Cuff